ANALISIS KESIAPAN RUMAH SAKIT DALAM PENGELOLAAN INVENTARISASI BARANG DENGAN SISTEM BARCODE DI RSUD dr. LOEKMONO HADI KUDUS - Aufir Amalia; Antono Suryoputro; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2016)
Demand for of goods in the dr. Loekmono Hadi Kudus Hospital with ahigh, abundance quantity and type of goods as well as fast mobility was needed. Ultimately, the planning and procurementof goods as well as the goods inventory in the hospital are not optimal yet. The purpose of this study was to determine the readiness of input, process and output in the hospital dealing with the management of goods inventory with a barcode system in dr. Loekmono Hadi Hospital Kudus. This was a qualitative research using intensive interviews and observation with the main informants of Goods Management Staff, Goods Storage Coordinator, Goods Storage Staff and triangulation informants of Household subsection Head and IPSRS Head. The results showed that dealing with input, the human resources are lacking in competence. Furthermore,regarding to infrastructure, therewas the unavailability of label printers and barcode scanners, the information system is not good enough, the absence job descriptionsof officers duties and function, and the lack of SOP. Dealing with the process, the planning aspect included the socialization that had been conducted, the organizing aspect covered the duties and function and SOP that had not been organized, the implementation of education and training that had not been conducted specifically by the hospital but had been given by the programmer, and the accountability report assessment of barcode system preparation. Regarding to the output, the readiness of hospitals was not well prepared due to the lack of human resources, the infrastructure was not complete, and the information system, the duties and function officers and SOP was unavailable. The suggestions in this research are to increase the understanding and competences of officers, develop the descriptions of duties and function and SOP as well as conduct specific training by the hospital regarding to the goods inventory management with barcode system.